The neurobiology of decision making: a window on cognition - Shadlen, Michael N. (Henry Stewart Talks, 2011)
Neurobiology, Decision making, Neural mechanisms of decision making, Perceptual decisions, Representation of evidence in visual cortex (area MT/V5), Direction selective neurons, Representation of accumulated evidence in parietal cortex, Lateral intraparietal area (LIP), Bounded evidence accumulation, Diffusion models of decision making, Confidence and "degree of belief", Post-decision wagering, Probabilistic reasoning, A neural mechanism for reasoning, log likelihood ratio, Decision making as a window on cognitive function in general, Intentional framework for information processing